ANALYTICAL REVIEW OF THE METHODOLOGY OF COMPUTER MODELING - M. D. Omarov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
The application of computer modeling gives additional incentives of development to the branches of science, helps to limit intuitive speculative modeling and expands the appendix of rational methods of information technologies. The review of methodology of computer modeling has been offered, the basic concepts of computer modeling have been given, the methodology of algorithms of stage-by-stage and step-by-step modeling has been also given.